Long-term mode shape degradation in large mode area Yb-doped pulsed fiber amplifiers. (22nd November 2016) - Bobkov, K K; Bubnov, M M; Aleshkina, S S; Likhachev, M E
Abstract: Experimental observation of long-term output mode shape degradation in pulsed Yb-doped fiber amplifiers is reported for the first time. The process occurs in large mode area Yb-doped fibers and is caused by the formation of the long period grating responsible for power transfer from the fundamental mode to the first high-order mode. The linkage between the process and photodarkening was revealed.